Construction Safety Risk Assessment for Underground Structures in Military Hospital Projects Using Activity-Based Failure Mode and Effects Analysis (FMEA) - Pungky Dharma Saputra; Muhammad Hamzah Fansuri; Anasya Arsita Laksmi; M Ragil; Madeline Nauli Basa Simbolon (Engineering Proceedings)
The Indonesian government is currently focusing on infrastructure development, including military infrastructure to strengthen national defense. One of these projects is the development of the Indonesian Army Central Hospital, which is being continually expanded with facilities such as proton beam therapy. Due to its underground construction, special attention must be given to construction safety to prevent workplace accidents. This study focuses on assessing construction safety risks at the military hospital using activity-based failure modes and effects analysis (FMEA). The research methodology employed is a mixed-method approach involving 5 construction safety experts and 100 respondents directly involved in underground structure construction. Descriptive data analysis was conducted, serving as the basis for calculating risk priority numbers (RPN) using the FMEA method. Three main activities were identified with very high risks ranked from 1 to 10: lifting of contiguous pile casing, basement excavation, and installation of cast in situ bored pile gutter. These activities entail safety risks with RPN values ranging from 100 to 125, including worker’s hands being caught in tools/materials, being struck by tools/materials, falling/slipping into excavations, and being buried/struck by excavated soil. This research has positive implications as a reference for developing construction safety plans that include risk identification, risk assessment, and determination of control measures.